Integrated coconut farming system for stable income - Maheswarappa, H P; Subramanian, P; Chowdappa, P (Indian Horticulture, 2018)
Coconut gardens offer excellent opportunities to exploit the interspace potential for maximizing return per unit area. Coconut-based cropping/farming systems involving cultivation of compatible crops in interspaces of coconut and integration with other enterprises like dairying offer considerable scope for increasing production and productivity per unit area, time and inputs by more efficient utilization of resources like sunlight, soil, water and labour. In humid tropics, higher efficiency of utilization of the basic resources of crop production, land, solar radiation and water can be achieved by adopting intensive cropping systems. Cropping/farming system aims at crop diversification and intensive cropping in the interspace available in coconut to increase the per palm productivity as well as productivity of unit holding in a system approach wherein the available farm resources like soil and water/rainfall resource, farm labour, agricultural inputs (seeds, fertilizers, agro-chemicals) etc. are utilized to produce both nuts, food and non-food agricultural products from the farm, in a business or profitable way. Under such a cropping/farming system, all the management practices and component production systems should be able to maintain high productivity, profitability and sustainability of existing coconut palms to maximize economic yield of the farm. Sustainability is the main objective of farming system, where production process is optimized through efficient utilization of the inputs in safeguarding the environment.